The effect of capture, confinement and immobilisation on acute phase protein, ands immune and haemostatic responses in the impala (Aepyceros melampus) - Brown, Kelsey Lee (My University, 2017)
Background: Environmental and anthropogenic disturbances have a variety of direct and indirect impacts on wildlife. Various methods have been proposed to identify and quantify stressors that negatively impact wildlife. Objectives: In this review, we examined the physiological stress response elicited during capture, confinement, and immobilisation on the acute phase response (APR), and immune and haemostatic responses in the impala. Method: Blood- and faecal-centric approaches were used to determine: (1) the hypothalamicpituitary-adrenal (HPA) axis activity by measuring cortisol in blood using a radioimmunoassay (RIA) and faecal glucocorticoid metabolites (FGM) using an RIA for corticosterone validated in many species, (2) the innate immune activity by measuring the circulating levels of leukocytes using manual white blood cell (WBC) counts and a haemocytometer, and leukocyte coping capacity (LCC) in response to challenges using reactive oxygen species (ROS) assay, (3) the secretion of acute phase proteins (APP) by measuring circulating levels of haptoglobin (Hp) and serum amyloid A (SAA) using an enzyme-linked immunosorbent assay (ELISA), and (4) the coagulation potential by measuring the intrinsic pathway using an activated partial thromboplastin time (aPTT) assay, the extrinsic pathway using a prothrombin time (PT) assay, fibrinogen conversion using a thrombin time (TT) assay, and fibrinogen concentration using a fibrinogen assay. Results: In response to the chronic effects of confinement and the repeated stress of immobilisation we observed an initial increase in HPA activity and common coagulation pathway activity, and resultant depletion in body reserves. There was a decline in HPA activity as the trials progressed and corresponding immunesuppression. Thereafter, as animals habituated to stressors, we found that several of the parameters measured in the impala showed recovery to initial levels (including body weight and condition, FGM concentration, ROS generating capability of whole blood, and coagulability). In response to 30 min of immobilisation the impala showed decreased HPA activity and coagulability, and immune-enhancement. IV Conclusion: These results demonstrate the feasibility of using physiological examinations to progress the understanding of short- and long-term impacts of anthropogenic disturbances on wildlife fitness, and improve animal welfare during conservation interventions.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science (Med) Wildlife Stress Physiology, 2017
Keywords: Depression, Mental--Pathophysiology